2017
DOI: 10.1371/journal.pone.0180496
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between information carrying words, memory and language skills in school age children with specific language impairment

Abstract: The receptive language measure information-carrying word (ICW) level, is used extensively by speech and language therapists in the UK and Ireland. Despite this it has never been validated via its relationship to any other relevant measures. This study aims to validate the ICW measure by investigating the relationship between the receptive ICW score of children with specific language impairment (SLI) and their performance on standardized memory and language assessments. Twenty-seven children with SLI, aged betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…It should also be pointed out that the WISC-R Verbal IQ scale is made up of other subscales that assess general cognitive skills, such as Verbal arithmetic; as a result, our Verbal IQ variable may be less specific to expressive and receptive language skills in particular. It is known that other cognitive processes, such as verbal memory (Frizelle et al, 2017), are considerable confounds of receptive language common in preterm born children (Vohr, 2014). Since both language measures used in the present study primarily assess receptive language, the lack of data on wider cognitive processes may play a role in our results.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be pointed out that the WISC-R Verbal IQ scale is made up of other subscales that assess general cognitive skills, such as Verbal arithmetic; as a result, our Verbal IQ variable may be less specific to expressive and receptive language skills in particular. It is known that other cognitive processes, such as verbal memory (Frizelle et al, 2017), are considerable confounds of receptive language common in preterm born children (Vohr, 2014). Since both language measures used in the present study primarily assess receptive language, the lack of data on wider cognitive processes may play a role in our results.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention also provides opportunity for further assessment of the child’s speech, language and communication skills. For example, TAs typically assess the child’s receptive language skills through play-based key word assessment, which has been shown to be a valid measure of receptive language (Frizelle et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies point out that there may be innate neurological deficits in linguistic processing mechanisms and that this impairment may be associated with limited information processing by verbal memory ( 10 ) . Recently, another study ( 11 ) suggested that there is a memory deficit specifically related to lexical processing that may result in comprehension deficits in children with DLD.…”
Section: Introductionmentioning
confidence: 99%